La fundamentación ontológica de la relación entre memoria e historia en La memoria, la historia, el olvido de Paul Ricoeur - Lythgoe, Esteban (2011)
“The Ontological Foundation of the Relationship between Memory andHistory in Paul Ricoeur’s Memory, History, Forgetting”. This paper will analyze PaulRicoeur’s Neo-Kantian proposal to articulate memory and history. The first step isto consider the concept of representation as a way to make both means of referringto the past comparable. In the next step, these two types of representationsare articulated by leading back to Heidegger’s temporal ontology. Amongst otherconsequences of this foundation, it follows that the possibilities of past agentscan be reinterpreted in the present. This situation legitimizes the impossibility ofsetting fixed rules for the articulation between memory and history. Finally, thispaper will discuss whether the philosopher does, or does not, commit a fallacyof composition, since his description is based on a specific form of history, whilehis prescriptions seem to have a general reach.